2010
DOI: 10.1089/fpd.2009.0526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Growth Temperature and Agar Versus Liquid Media on Freeze–Thaw Tolerance ofYersinia enterocolitica

Abstract: Yersinia enterocolitica is a foodborne pathogen well known for its ability to grow at low temperatures. Recent studies with another psychrotrophic foodborne pathogen, Listeria monocytogenes, revealed that temperature of growth had pronounced impact on survival following repeated freezing and thawing (cryotolerance). Listerial cryotolerance was significantly more pronounced when bacteria were grown at 37 degrees C than following growth at either 4 degrees C or 25 degrees C. However, it is not known whether such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Repeated freeze-thaw cycles generally lead to greater inactivation and lower microbial concentrations, but pathogens may survive, i.e. be cryotolerant; defined as the ability to survive repeated cycles of freeze thawing (Azizoglu and Kathariou, 2010). Actively growing bacteria are more susceptible to freeze-thaw inactivation than stationary phase cells (e.g.…”
Section: Freezing and Thawing Effects On Survival And Growth Of Pathogenic Microorganismsmentioning
confidence: 99%
“…Repeated freeze-thaw cycles generally lead to greater inactivation and lower microbial concentrations, but pathogens may survive, i.e. be cryotolerant; defined as the ability to survive repeated cycles of freeze thawing (Azizoglu and Kathariou, 2010). Actively growing bacteria are more susceptible to freeze-thaw inactivation than stationary phase cells (e.g.…”
Section: Freezing and Thawing Effects On Survival And Growth Of Pathogenic Microorganismsmentioning
confidence: 99%
“…Enteropathogenic Yersinia are foodborne pathogens. Therefore it comes as no surprise that they thrive at refrigeration temperatures (Brocklehurst and Lund, 1990; Goverde et al, 1994; Azizoglu and Kathariou, 2010; Keto-Timonen et al, 2018), and in this environment even remain primed for infection (Asadishad et al, 2013). To understand the molecular mechanisms by which psychotropic Yersinia thrive in cold environments may give rise to strategies by which growth can be restricted, and this would be a strategically important preventative measure for the food processing industry.…”
Section: Niche Adaptationmentioning
confidence: 99%
“…Yersinia enterocolitica is capable of growing at temperatures approaching and even below 0 • C (Tudor et al, 2008;Divya and Varadaraj, 2013). Therefore, even refrigeration temperatures (0-4 • C) can allow significant bacterial growth over time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, even refrigeration temperatures (0-4 • C) can allow significant bacterial growth over time. Several studies have reported growth of Y. enterocolitica in food products stored at refrigeration temperatures: e.g., on raw beef, with increased cell counts of up to 2 log CFU/ml within 4 days (Tudor et al, 2008) and in pasteurized milk, reaching levels of 5-7 log CFU/ml after 7 days (with an initial inoculum of 1-3 log CFU/ml) (Amin and Draughon, 1987).…”
Section: Introductionmentioning
confidence: 99%